COMMUNITY POLICING AS A CORRELATE OF EFFECTIVE SECURITY IN OYO STATE, NIGERIA (2019)
The incessant incidents of breakdown of law and order as well as the persistent threats to life and property have shown the lapses in the regular policing system in Nigeria. This trend, therefore, led to the introduction of Community Policing Approach (CPA) in Oyo State in February, 2004 as an alternative strategy to ensure effective security (Prevention of Crimes (PoC), Early Detection of Crimes (EDoC), Apprehension of Offenders (AoO), Protection of Life and Property (PoLP), and Enforcement/Preservation of Law and Order (EPoLO). However, since its introduction, there has not been an independent assessment of CPA’s successes as available reports have been self-reported by the Nigeria Police Force. This study was, therefore, carried out to assess the impact of the CPA (Police-Community Relations (PCR), Police-Community Joint Patrol (PCJP), Police-Community Accountability (PCA) and Intelligence Gathering/Sourcing (IGS) on Effective Security (ES) in Oyo State, Nigeria. This is with a view to having an independent assessment of ES. The Normative Sponsorship and Broken Window theories served as the anchor, while the descriptive survey design was employed. The 12 Local Government Areas (LGAs) where the CPA was introduced in Oyo State were enumerated. In each LGA, the leaders and active members of groups involved in CPA were purposively selected: market associations (115), community development associations (120), vigilante groups (144), Police Community Relations Committee’s (PCRC) (132), community and religious leaders (146) and landlord associations (144). Twenty police officers involved in CPA in each LGA were randomly selected. Different CPA and ES scales were administered to the community and the police. The ES (r=0.87) and CPA (r=0.75) questionnaires with five and six subscales respectively were used for data collection. These were complemented with two key informant interview sessions with the LGA Chairman and Divisional Police Officer/PCRC desk officer in each LGA. The quantitative data were analysed using descriptive statistics, Pearson product moment correlation and multiple regression at 0.05 level of significancewhile qualitative data were content analysed. The six platforms for the CPA were ranked: market associations (92.5%), vigilante (92.2%), public office holders (91.2%), PCRC (87.5%), community and religious leaders (87.3%) and landlord associations (86.3%). The acceptability of CPA’s and ES‘s components was rated high: IGS (88.7%), PCR (87.2%), PCJP (86.4%), PCA (85.1%): AoO (93.2%), EDoC (87.7%), EPoLO (84.5%), PoLP (53.4%) and PoC (50.2%). The IGS (r=0.54), PCR (r=0.41), PCA (r=0.41) and PCJP (r=0.40) had significant correlations with ES. The CPA had a significant joint prediction on ES (F(4,1036)=80.67, adj.R2=0.40); accounting for 40.0% of its variance. Only PCJP (β=-0.19) significantly contributed to ES, while other components did not. Lack of adequate knowledge of CPA and age-long distrust affected the general composition to and acceptability of CPA. The introduction of community policing approach, particularly police-community joint patrol had positively influenced effective security in the sampled communities of Oyo State, Nigeria.